Poetics of Ljubomir Micić and Branko Ve Poljanski’s hybrid multigenre poetic texts - Đurić, Dubravka (Poznańskie Studia Slawistyczne, 2012)
In the text I will focus on Zenitist poetry by Ljubomir Micić and Branko Ve Poljanski. I will construe a new discursive framework, which will make it possible for us to understand their multigenre  texts  as important  items  in  the  national poetry  canon.  I  will  contextualize  the general characteristics of European avant-garde poetry practices, which were used by Micic and Poljanski in order to interpret the specific place of Zenitism as a general Balkan avantgarde movement, participating in a significant way in the European and world avant-garde.